1970
DOI: 10.1002/bs.3830150605
|View full text |Cite
|
Sign up to set email alerts
|

Judgment policy and interpersonal learning

Abstract: In a study of interpersonal learning, 96 Ss were asked to predict another person's judgments about the socio-economic growth of a series of underdeveloped nations. Following each prediction, Ss were informed of the actual judgment made by the person (or Target)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…First, we assume the reader is familiar with the MCPL paradigm; several excellent reviews are readily available (Brehmer, 1980;Hammond et al, 1980). In addition, the review is essentially limited to research on metric MCPL tasks with individuals, thereby excluding research on CFB in nonmetric tasks (Castellan, 1974;Castellan & Swaine, 1977), studies of cognitive conflict (Hammond, 1973) and interpersonal learning (Summers et al, 1970), and group decision making (Deane, 1979;Rohrbaugh, 1979Rohrbaugh, , 1981; we have, however, referred to these studies when they are directly relevant to a particular issue. Finally, because an essential purpose of this article is to determine the role of the cognitive component of CFB, the studies reviewed are only those that provide some form of Cl; we have not exhaustively reviewed Tl-only studies, but we refer to such studies when they are particularly relevant.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we assume the reader is familiar with the MCPL paradigm; several excellent reviews are readily available (Brehmer, 1980;Hammond et al, 1980). In addition, the review is essentially limited to research on metric MCPL tasks with individuals, thereby excluding research on CFB in nonmetric tasks (Castellan, 1974;Castellan & Swaine, 1977), studies of cognitive conflict (Hammond, 1973) and interpersonal learning (Summers et al, 1970), and group decision making (Deane, 1979;Rohrbaugh, 1979Rohrbaugh, , 1981; we have, however, referred to these studies when they are directly relevant to a particular issue. Finally, because an essential purpose of this article is to determine the role of the cognitive component of CFB, the studies reviewed are only those that provide some form of Cl; we have not exhaustively reviewed Tl-only studies, but we refer to such studies when they are particularly relevant.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…Nystedt and Magnusson (1973) had their subjects predict grades in introductory psychology. Other task contents have included the prediction of socioeconomic growth for hypothetical underdeveloped countries (Summers, Taliaferro, & Fletcher, 1970), the order of finish in horse races (Rohrbaugh, 1979, 1981), and fictitious medical diagnosis tasks (Brehmer & Johansson, 1977; Brehmer & Qvarnström, 1973; Lindell, 1976).…”
Section: Task Contentmentioning
confidence: 99%
“…However, there is less agreement on the question of what information should be included in effective feedback. Past research has clearly indicated that outcome-based feedback does not lead to improvement in task performance, (Deane, Hammond, & Summers, 1972;Hammond, 197 1 ;Summers, Taliaferro & Fletcher, 1970;Todd & Hammond, 1965) and in some cases can actually hinder performance (Hammond, Summers, & Deane, 1973). Thus, researchers have tumed to evaluating process-based feedback.…”
Section: Introductionmentioning
confidence: 99%
“…While some have claimed that the discrepancy between self-reported and applied decision-making policies demonstrate a lack of self-insight (e.g., Summers, Taliaferro, & Fletcher, 1970;Ullman & Doherty, 1984) and an inability to access cognitive processes (Nisbett & Wilson, 1977), others note that self-reported decision-making may be biased by social desirability and the limits of memory (Brookhouse, Guion, & Doherty;1986;Shepard6031416991, 1964). Future research could explore if the self-reports represent a genuine lack of insight or if they reflect a bias in reporting.…”
Section: Police Discretion In Rape 22mentioning
confidence: 99%